Rabindranath Tagore, the singer and his song - Shome, Reba. (Gurgaon, Haryana, India : Penguin Books, 2017)
On the musical works of Rabindranath Tagore, 1861-1941, Bengali litterateur, and his life from the perspective of music.
Accompanied by CD-ROM of Tagore's songs.
Includes bibliographical references (pages 197-228) and index.
Donated By Akbar Ali Khan
Keywords: Tagore, Rabindranath, -- 1861-1941 -- Criticism and interpretation; Tagore, Rabindranath, -- 1861-1941 -- Musical settings -- History and criticism; Bengali literature